Legal Development in Strengthening National Resilience Based on the Indonesian Constitution - Fransisco, Wawan; Yahya, Fuchry; Syam, Fauzi (IHSA Institute, 2023)
Legal development is not something that stands alone, but is integrated with development directions in other fields that require harmonization. Even though the direction of legal development is based on the outlines of ideas in the 1945 Constitution of the Republic of Indonesia, it requires alignment with the level of development of society that is envisioned to be created in the future.. This research was carried out using a normative juridical method which was carried out through a literature study which examined secondary data, namely statutory regulations, research results, scientific journals, study results and references. From the research results, it can be seen what the direction of legal development is and creating strong national resilience. There are still various legal loopholes, especially regarding laws and regulations that regulate territorial issues and state sovereignty. For this reason, law enforcement is a process that must be carried out in accordance with applicable laws and regulations without forgetting our conscience as humans. Law enforcement must be carried out in good faith to build a society with a legal culture.policies